Cogeneration topology for wind energy conversion system using doubly‐fed induction generator. Issue 7 (1st June 2016) - Parida, Adikanda; Chatterjee, Debashis
Abstract : A novel wind energy conversion system (WECS) with cogeneration topology is presented in this study. In the proposed scheme, doubly‐fed induction generator (DFIG) is used as the major source for power generation in grid‐isolated mode. The wind turbine operated DFIG is integrated with a permanent magnet ac generator and a solar photovoltaic (PV) module to supplement the both rotor power requirement of DFIG and part of the average load power demand. The performance of a grid‐isolated WECS, over wide speed range can be significantly improved through the sequential extraction of wind power along with an augmented solar PV source. The proposed scheme is economically viable with feasible unit cost of generated power. The control scheme has been simulated and experimentally validated with a practical 2.5 kW DFIG using dSPACE DS1104 module, which produced satisfactory results.